Emerging the Submerged Realities of Mass Rape in the News of May 1998 Riot - Kezia Sola Gratia (UPT Publikasi Ilmiah UNISBA, 2024)
This study employs agenda-setting and media fragmenting theory alongside critical analysis of discourse studies (CADS) to scrutinize media dynamics during the May 1998 Riots in Indonesia. Agenda-setting and Media Framing theories analyze how the media prioritizes and frames specific issues. At the same time, CADS provides a method to present a detailed examination of language and representation in media texts. By analyzing 296 and 261 news articles from two of the most prominent Indonesian online newspaper platforms, the study investigates the submersion of discourses on gender and ethnic violence. Utilizing CADS, the research conducts frequency, collocation, concordance, cluster, and keyword analyses to uncover hidden narratives of gender and ethnic violence within the riot coverage. The analysis reveals significant gaps in discourse on racial and gender-based violence, highlighting the importance of identifying underlying narratives in news coverage. Additionally, the study underscores a void in the coverage of gender and ethnic violence discourses related to the May 1998 Riots, suggesting potential oversight or suppression of crucial aspects. This highlights the media's dual role as a reflector of events and an active influencer of public narratives.